Implementasi Inverse Kinematics Pada Robot Lengan Untuk Pengambilan Benda Dengan Koordinat Awal Acak - Ricky Zefani Aria Zurendra; Rizal Maulana; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The increasing of enthusiasts in e-commerce activities have increased the flow of incoming and outgoing goods in storage areas. The storage activity certainly requires a considerable amount of time and energy so a system is needed to retrieve and place items automatically. This system is equipped with a Raspberry Pi Rev1.3 camera as a room camera that is capable of taking object pictures underneath. The camera integrates with the Raspberry Pi 3 as a processing unit so the types and initial coordinates of objects can be recognized by the system. Both of the object's information will be sent to the OpenCM 9.04 microcontroller as a parameter to place the object into the specified location. Objects displacement was carried out using a 3 DoF robot arm composed by five Dynamixel AX-12A servo motors, three servo motors as determinants of system motion and the remaining two were used to grip objects. The movement of the 3 DoF robot arm is based on the calculation of objects coordinate by using inverse kinematics method to produce angular values for the three servo motors. The testing results of the inverse kinematics method on this system's robot arm movement has an error percentage of 10.10%. As for overall testing, out of 40 tests, this system has a 95% success rate with an average computation time of 8.446 seconds.